PUBLIC HEALTH AND ENVIRONMENTAL IMPACT OF HEAVY METALS IN BOTTOM COAL ASH - I OshatuyiI; R. A Ibrahim; F D Egwuje; X H I Abdullahi H I (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
There have been great public health and environment concerns on the concentration of heavy metals especially those present in bottom coal ash as they could have impact on the well-being of humans and other living things. This study examined the toxicity and utility of heavy metals in bottom coal ash and their public health and environment impacts by evaluating the heavy metal concentration, toxicity, and utility of bottom coal ash. The concentration of heavy metals was determined using an atomic absorption spectrometer (AAS). Findings from this study indicated that while other elements were within the WHO’s allowable level and have significant biochemical functions to living organisms, the percentage of lead present in the bottom coal ash was approximately 0.0016%, or 167 mg/kg, which is far too high by WHO standard. Through the process of bioaccumulation, this could result in lead toxicity. The study thus recommended that this substance be properly handled and treated to safeguard public health concerns and reduced negative environmental impacts especially in areas where bottom coal ash is deposited.